REMOVAL OF ORGANIC COMPOUNDS FROM WASTEWATER USING MONTMORILLONIT AND ACTIVATED CARBON NANOMCOMPOSITE - Timothy, Phinehas
Water pollution continues to escalate with the growth of industrial activities carried out by humans. One of the mitigation efforts to reduce water pollution is wastewater treatment. Adsorption is a commonly used method in wastewater treatment. Restiawaty et al. (2021) have previously performed adsorption using montmorillonit-activated carbon-alginat nanocomposites to separate GE and MCPD contaminants from RBDPO. This study aims to test an adsorbent made from the same raw materials to remove organic compounds such as methylene blue and rhodamine B from wastewater. This research is conducted to determine the optimal composition of montmorillonit, activated carbon, and alginat for achieving the best adsorption efficiency, as well as to characterize the adsorbent. The study also investigates the impact of various variables on the adsorption performance of the adsorbent using both batch and continuous reactors. Batch experiments revealed that an adsorbent with a MMT:AC ratio of 1:1:1 exhibited the highest efficiency with an adsorption duration of 120 minutes. Adsorption of a Methylene Blue solution at 248 mg/L resulted in a removal percentage of up to 82%, while adsorption of a Rhodamine B solution at 213 mg/L achieved a removal percentage of up to 58%. The adsorbent, consisting mainly of carbon, oxygen, and calcium, has an average pore size of 2.997 and a compressive strength of 4.31 N/mm². Continuous method experiments showed that flow rate significantly affects the removal percentage, with the lowest flow rate (22 mL/second) providing the best adsorption performance. Optimal adsorption conditions were achieved at the highest column height (1.5 cm) with the longest breakthrough time (4.94 minutes) and saturation time (230 minutes). The MMTNA-Alginat nanocomposite exhibits breakthrough and saturation times similar to those of comparable adsorbents, but the qmax remains lower